2019
DOI: 10.3390/f10090722
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Classification of the ABC Transporter Family in Betula halophila and Expression Patterns in Response to Exogenous Phytohormones and Abiotic Stresses

Abstract: ATP-binding cassette (ABC) transporters comprise a transport system superfamily which is ubiquitous in eukaryotic and prokaryotic cells. In plants, ABC transporters play important roles in hormone transport and stress tolerance. In this study, 15 BhABC transporters encoded by genes identified from the transcriptome of Betula halophila were categorized into four subfamilies (ABCB, ABCF, ABCG, and ABCI) using structural domain and phylogenetic analyses. Upon B. halophila exposure to exogenous phytohormones and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 35 publications
1
8
0
1
Order By: Relevance
“…The Arabidopsis ABP, AtABCG25/WBC26 transporter, is an ABA efflux carrier, and its overexpression reduced the water loss by facilitating ABA delivery to guard cells 88 ; similarly, expression of AtABCG36 in transgenic Arabidopsis plants contributed to drought stress and salt resistance 89 . An increased level of ABP and GBP was observed in Arabidopsis and Betula halophila plants under drought stress, and the significant increase in ABP is consistent with the increased activity of ATPase 90 , 91 . Thus, all three date palm cultivars opted for similar molecular mechanisms to mitigate the drought stress by overexpressing the ABP-associated ESTs.…”
Section: Discussionsupporting
confidence: 63%
“…The Arabidopsis ABP, AtABCG25/WBC26 transporter, is an ABA efflux carrier, and its overexpression reduced the water loss by facilitating ABA delivery to guard cells 88 ; similarly, expression of AtABCG36 in transgenic Arabidopsis plants contributed to drought stress and salt resistance 89 . An increased level of ABP and GBP was observed in Arabidopsis and Betula halophila plants under drought stress, and the significant increase in ABP is consistent with the increased activity of ATPase 90 , 91 . Thus, all three date palm cultivars opted for similar molecular mechanisms to mitigate the drought stress by overexpressing the ABP-associated ESTs.…”
Section: Discussionsupporting
confidence: 63%
“…Stress in plants creates hormonal imbalances, leading to distorted metabolic function and interfering with plant growth and development. In response to stress, plants often adjust various physiological functions to accommodate or compensate for the affected hormone and adapt to harsh environmental conditions ( An et al, 2019 ). A candidate gene, TraesCS6A01G353700 , located on chromosome 6A, codes for Chlorophyllide a oxygenase (CAO), which plays a critical role in stress-related responses.…”
Section: Discussionmentioning
confidence: 99%
“…Deppe et al (2018) identified the ABC transporter Lr34 from wheat and reported its potential role in manipulating the composition of phospholipids in the plasma membrane and triggering the biotic and abiotic stress response in barley. Similarly, An et al (2019) observed significant changes in the expression of genes belonging to the ABC transporter family (ABCB and ABCG subfamilies) in response to exogenous phytohormones treatment and abiotic stresses. Their gene expression was reported to be linked with ABA‐dependent signaling pathways, which play an important role in modulating the stress tolerance level.…”
Section: Functions Of Abc Transporters In Heat Stress Tolerance Of Plantsmentioning
confidence: 91%
“…ABC transporters have been characterized in other plant models. For example, in Betula halophile , a model plant that survives under extreme salinity and drought conditions, has 15 diverse ABC transporter genes (An et al, 2019). The identified ABC transporters were classified into four sub‐families: ABCB, ABCG, ABCF and ABCI.…”
Section: Classification Of Abc Transporters and Their Structuresmentioning
confidence: 99%
See 1 more Smart Citation